2016
DOI: 10.29244/jji.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Efek Sinergis Bahan Aktif Tanaman Obat Berbasiskan Jejaring Dengan Protein Target

Abstract: Medicinal plants contain inherently active ingredients. Such ingredients are beneficial to prevent and cure diseases, as well as to perform specific biological functions. In contrast to synthetic drugs, which is based on one single chemicals, medicinal plants exert their beneficial effects through the additive or synergistic action of several chemical compounds. Those chemical compound act on single or multiple targets (multicomponent therapeutic) associated with a physiological process. Active ingredients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Apparently, because the two ingredients have the same high effect, a synergistic effect was observed when the two were combined. This is in line with research reported by Syahrir et al [37] which states that the combination between active ingredients can show a synergistic.…”
Section: α-Amilase Inhibitionsupporting
confidence: 93%
“…Apparently, because the two ingredients have the same high effect, a synergistic effect was observed when the two were combined. This is in line with research reported by Syahrir et al [37] which states that the combination between active ingredients can show a synergistic.…”
Section: α-Amilase Inhibitionsupporting
confidence: 93%
“…This allegedly happened because of the saturation factor of the extract at specific doses. Several components of active compounds in plants are simultaneously involved in therapy, thus enabling these active compound components to have a synergistic or antagonistic effect (Syahrir et al, 2016). Thus, the synergistic effect that occurs can increase concentration to the saturation point.…”
Section: Resultsmentioning
confidence: 99%
“…It was predicted that the SEJ extract contains quercetin and coniferin compounds, the SCJ extract contains quercetin and juncusol compounds, and the SWJ extract, in addition to quercetin, contains retucine. Although all locations were predicted to contain quercetin compounds, which are known to have antidiabetic activity, the level of activity of extracts from each region is different because of the interaction of quersetin compounds with other compounds that can be antagonistic-decreasing activity-or synergistic-strengthening activity (Syahrir 2016).…”
Section: Fourier Transform Infrared Analysis (Ftir)mentioning
confidence: 99%